Dorothy Day and the Catholic Worker : The Miracle of Our Continuance - Day, Dorothy, 1897-1980; Cherry, Vivian, 1920-2019; Hennessy, Kate, 1960- (Book collections on Project MUSE., 2016)
"A portrait of Dorothy Day and the Catholic Worker movement in New York City through photographs taken in 1955 by Vivian Cherry, a documentary photographer, accompanied by excerpts of Dorothy Day's writings selected and edited by her granddaughter, Kate Hennessy"--